Effects of feed iodine concentrations and milk processing on iodine concentrations of cows' milk and dairy products, and potential impact on iodine intake in Swiss adults. Issue 2 (24th July 2019) - van der Reijden, Olivia L.; Galetti, Valeria; Herter-Aeberli, Isabelle; Zimmermann, Michael B.; Zeder, Christophe; Krzystek, Adam; Haldimann, Max; Barmaz, Andrea; Kreuzer, Michael; Berard, Joel; Schlegel, Patrick
Abstract: The contribution of milk and dairy products to daily iodine intake is high but variable in many industrialised countries. Factors that affect iodine concentrations in milk and dairy products are only poorly understood. Our aim was to: (1) assess the effect of feed iodine concentration on milk iodine by supplementing five groups of five cows each with one of five dosages from 0–2 mg iodine/kg DM; (2) quantify iodine losses during manufacturing of cheese and yogurt from milk with varying iodine concentrations and assess the effect of cellar-ripening; and (3) systematically measure iodine partitioning during heat treatment and skimming of milk. Milk iodine reached a near-steady state after 3 weeks of feeding. Median milk iodine (17–302 μg/l for 0–2 mg iodine/kg DM) increased linearly with feed iodine ( R 2 0·96; P < 0·001). At curd separation, 75–84 % of iodine was lost in whey. Dairy iodine increased linearly with milk iodine (semi-hard cheese: R 2 0·95; P < 0·001; fresh cheese and yogurt: R 2 1·00; P < 0·001), and cellar-ripening had no effect. Heat treatment had no significant effect, whereas skimming increased ( P < 0·001) milk iodine concentration by only 1–2 μg/l. Mean daily intake of dairy products by Swiss adults is estimated at 213 g, which would contribute 13–52 % of the adults' RDA for iodine if cow feed is supplemented with 0·5–2 mg iodine/kg DM. Thus, modulation of feed iodine levels can help achieve desirable iodine concentrations in milk and dairy products, and thereby optimise their contribution to human iodine nutrition to avoid both deficiency and excess.